O PEDAGOGO NA ORGANIZAÇÃO DO TRABALHO PEDAGÓGICO COM ÊNFASE NO PLANEJAMENTO DA ESCOLA ITINERANTE CAMINHOS DO SABER - Silva, Luciana Maria de Matos e (2018)
The present work brings a study about the educator’s work in the organization of teaching, in the experience of implementation of Political Pedagogical Project at the itinerant school Caminhos do Saber. It is a research developed at the Post Graduation Program in Teaching studies at Centro-Oeste Paraná State University (UNICENTRO), between 2016 and 2018. It aims at understanding the teaching work in the teaching organization of the itinerant school Caminhos do Saber, from the implementation of Human Formation Studies with Study Compounds; It also aims at getting to know the history of Pedagogy in Brazil and the contradictions of the educator’s work in public schools in Paraná; It points out the main roots of Education of MST (landless workers movement), as well as the pedagogical fundaments in which it is constituted; It analyzes the educator’s job in the organization of his/her work with focus on school planning of itinerant school Caminhos do Saber. In the methodological field it uses the Marxism theory, with the analyzing categories: history, mediation, contradiction and totality. The Literature in this project bring authors such as Brzezinsky (2012), Saviani (2013), Haddad (2016) which approach the history of pedagogy in Brazil and in Paraná state; Caldart (2004), MST (1996), Camini (2009), contribute with the elements of education within MST and itinerant school; Paulo Freire (1980) contributes with the reflections about Freirean pedagogy; Pistrak (2000; 2009); Shulgin (2013); Krupskaya (2017) and Makarenko (1986) focus on socialist pedagogy; Freitas (2001) approaches discussions about the organization of pedagogy work. It analyzes documents at Political Pedagogical Project, Teaching Plan and interviews structured with educators who work in the pedagogical coordination of the itinerant school Caminhos do Saber, correlating the analyses with the field observation. The analysis considers the path of pedagogy course in Brazil and the complexity which involves the matter of identity and the pedagogical work in public schools of public teaching system of the state of Paraná. It also highlights the fundaments of education project of MST, the pedagogy of the movement, the Freirean pedagogy and the socialist pedagogy and thus, it points out the analysis of the educator’s role in the pedagogical proposal of itinerant school Caminhos do Saber. It concludes that pedagogical work is arranged by a group of elements which compose the itinerant school form, by periods of Human Formation and with complexes of study. It distinguishes that the educator and his/her job are essential to join the elements of resistance of this professional at school and in education, mediating the state calls and requests of the social movement. It considers that the educator has the challenge to guarantee the dialectic movement of the political pedagogical project in the relationship with the whole school, whether articulating content, life and work; the evaluation practices; the collective and interdisciplinary elaboration of planning by complex of studies; and, the student’s self-organization. It proposes that this profile of educator should contribute to improvements of school work, so the amount of MST and Brazilian education.